An Adaptive Fuzzy Control Method for Spacecrafts Based on T-S Model - Wang Qi; Gao Tian; He He (Institute of Advanced Engineering and Science, 2013)
A model reference adaptive control method is proposed for uncertain nonlinear characteristics of spacecraft attitude control system. This method combines fuzzy control methodology and nonlinear feedback linearization methodology, which made the closed-loop system stable and the state of fuzzy system track the state of reference model according to the parallel distributed compensation theory and the rational design of the fuzzy state feedback control law. The nonlinear closed-loop system was linearized by selecting fuzzy state feedback parameters and fuzzy membership function. Then an adaptive control law was designed by Lyapunov function. As a result the system can be adaptive to all kinds of parameter uncertainties and robust to modeling inaccuracy and external disturbance. Meanwhile, the simulation results indicate that the control law can quickly guarantee the stability of the spacecraft attitude and be robust to model perturbations and external disturbances. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3549